ICRP recommendations for recovery. Issue 1 (July 2021) - Kai, M.
In 2020, the International Commission on Radiological Protection (ICRP) issued Publication 146 which provides a framework of the radiological protection of people and the environment in the case of a large nuclear accident. Mitigation of radiological consequences is achieved using the fundamental principles of justification of decisions and optimisation of protection. These recommendations emphasise the importance of the optimisation of protection for the rehabilitation of living and working conditions in the affected areas during the intermediate and long-term phases. They underline the role of co-operation between the authorities, experts, and the affected population in the co-expertise process to facilitate informed decisions about their own protection. ICRP deﬁnes reference levels to be selected within generic bands of exposure considering the induced risk of radiation, as well as the feasibility of controlling the situation.